THE IMPLEMENTATION OF THE ENTITY CONCEPT IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) OF MARINE CAPTURE FISHERIES (A STUDY OF MR. NIKO’S MARINE CAPTURE FISHING BUSINESS IN LEMITO VILLAGE, LEMITO DISTRICT, POHUWATO REGENCY) - Aldi D. Komendangi; Mahdalena Mahdalena; Amir Lukum (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the implementation of the entity concept in Micro, Small, and Medium Enterprises (MSMEs) in the marine capture fisheries sector, focusing on Mr. Niko’s fishing business in Lemito Village, Pohuwato Regency. The entity concept, which emphasizes the separation between business and personal finances, is essential in producing reliable financial information and ensuring business sustainability. However, in practice, many small-scale fishermen still combine business and household finances, leading to difficulties in assessing financial performance. This research employs a qualitative descriptive approach to examine existing financial practices and evaluate the application of accounting principles based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Data were collected through observation, interviews, and documentation of financial transactions. The results indicate that prior to the intervention, the business applied a simple and manual recording system without structured financial statements and without implementing the entity concept. After applying SAK EMKM-based financial reporting, including the preparation of income statements and statements of financial position, the financial condition of the business became more transparent and measurable. The business recorded a net profit of IDR 11,449,235 and showed a balanced financial position. Furthermore, the implementation of the entity concept improved financial control, enabled accurate profit measurement, supported asset management planning, and increased credibility with external stakeholders. In conclusion, the application of the entity concept and standardized financial reporting significantly enhances financial management practices and contributes to the sustainability of MSMEs in the fisheries sector.